Backstepping control using nonlinear state observer for switched reluctance motor - Nha, Phi Hoang; Phi, Pham Hung; Thuy, Dao Quang; Dat, Pham Xuan; Hai, Le Xuan (Vietnam Journal of Science and Technology, 2022)
Switched reluctance motor (SRM) has many advantages with very strong nonlinearity, hence it is difficult to control. This paper presents a new method to control the speed of switched reluctance motor based on backstepping technique and nonlinear state observation. This controller is first applied for switched reluctance motor with nonlinear drive model. This model is a combination of both the commutator and the motor in the same model. The combined model of switched reluctance motor helps to reduce the influence of nonlinearity due to the switching lock, increasing the accuracy in controlling this motor. The state variables of the controller are approximated by nonlinear state observer, including speed observer, flux observer, and rotor position observer. The observer state variables are compared with directly measured state variables. This nonlinear state observer improves the switched reluctance motor drive system by reducing actual measuring devices, such as incremental encoder and torque transducer. The stability of the closed control loop was analyzed using Lyapunov stability criterion. The simulation is carried out with both traditional backstepping controller and the backstepping controller combined with nonlinear state observation. The quality of the nonlinear state observer and backstepping control system are analyzed theoretically and through numerical simulations.